Key performance indicators for ranking general hospitals in Iran - Ali Jajarmizadeh; Ali Mohammad Mosadeghrad; Ebrahim Jaafaripooyan (Payesh, 2025)
Objective(s): The quality of hospital services should be constantly monitored and enhanced. Key performance indicators (KPIs) are as such essential to strengthen the supervision of the government, people, and other health system stakeholders and improve hospitals' performance. The present study thus seeks to identify the KPIs for ranking general hospitals in Iran. Methods: This study adopted a mixed-method design at four stages. The researchers used a scoping review to identify the related indicators and frameworks in the literature. They further qualitatively identified local indicators for hospital ranking. An expert panel refined the pooled indicators, and the KPIs were finally prioritized using the decision matrix technique. Results: Initially 233 and then 84 indicators were identified. The final 50 indicators were determined and prioritized. The number of medical staff per bed, mortality rate, patient satisfaction, staff satisfaction, and bed occupancy rate were among the highest-priority indicators. Conclusion: Structure, process, and outcome-related indicators were proposed to rank general hospitals in Iran that could be utilized to strengthen the current hospital evaluation system. Using these indicators to evaluate and rank hospitals could hopefully improve transparency, public disclosure, organizational efficiency, and ultimately the quality of services.